Maximal motion and minimal matter: Aristotelian physics and special relativity. - Keck, John W. (Synthese, 2022)
This paper shows how key aspects of Aristotle’s core concepts of matter and motion, some of which have recently been shown to help make sense of quantum mechanical indeterminacy, align with some important results of the energy-momentum relationship of special relativity. In this conception, mobility and indeterminacy are inherently linked to each other and to materiality. Applying these ideas to massless particles, which relativity tells us move at the maximal cosmic speed, allows us to draw the conclusion that they must be the most basic physical bodies, that is, mobile substances (secondary, locomotive matter). The most familiar massless particle, the photon, constitutes light. Furthermore, because the photon composes luminous matter but cannot be decomposed into anything else more basic, it fulfills the definition of element.